Penerapan Layanan Bimbingan Klasikal Model Project-Based Learning (PjBL) untuk Identifikasi Karier Siswa Kelas X SMA Negeri 1 Taman - Muhammad Ali Najich; Yafi Hanif Hasbullah; Soffa Al Ma’wa; Intan Belqis Khumairoh; Mada Apriel Papin; Aisyah; Yupiter Sulifan (DA'WA: Jurnal Bimbingan Penyuluhan & Konseling Islam, 2025)
This study aims to analyze the implementation of Project-Based Learning (PjBL)-based classical guidance services in helping 10th-grade students of SMA Negeri 1 Taman identify career interests and talents. This type of research is a classroom action research that uses two cycles with 35 students of 10th-8th grade of SMAN 1 Taman as research subjects. The data collection method uses career identification, observation, and testing methods. From the analysis of the research data, it is known that in cycle I, the average value of students' career identification was 54.60%, increasing to 75.24% in cycle II. The implementation of classical guidance services using the project-based learning model can also increase the variety of job professions, where in cycle I, student activity was 56.24%, increasing to 78.25% in cycle II.